Factors Influencing Foreign Students' Choice of Institution (UUM)- Internet Marketing and Web Search Behavior - Aldrina @ Mimi, O.P. Andu (2009)
It is important that Higher Education Institutions recognized themselves as contributing in the service industry to meet with the increasing demand of their stakeholders. In competing globally, Malaysian institutions are becoming popular destination for overseas studies. This study attempted to empirically identify the relationship between internet marketing and foreign students’ web search behaviour towards their choice of institution.The study involved foreign students who were studying at Universiti Utara Malaysia(Northern Malaysian University). A total number of 288 valid responses were collected through questionnaire-based survey method representing a total of 96.97 per cent response rate. Hypotheses testing method were employed, and self-administered questionnaire with five-point Likert scale was used to collect the data. Data were analyzed through Pearson correlation and multiple regressions analysis. The results were there is a positive relationship between internet marketing and web search behaviour with foreign students’ choice of institution (UUM), hence hypotheses are accepted. Regression analysis indicated that web search behaviour explained more variance in foreign students’ choice of institution at r=0.477, p<0.01 in comparison to internet marketing. Practical implications, recommendations and future research were offered in this study.